Definiciones y mediciones como principios propios de las demostraciones científicas (Aristóteles y Tomás de Aquino) - Guzmán Vicente Burgoa, Lorenzo de ca. 21. Jh. (Sapientia, 2021)
Since all scientific knowledge is a derivative or mediate knowledge, it is necessary to investigate the principles or premises from which it must start; so that it is something immediate and somehow self-evident, closed, not endlessly provable. Thomas Aquinas, following and commenting on the systematic thought of the teacher Aristotle, proposes two series of principles: some of them, common, and others, specific to each scientific knowledge. Regarding the latter, it clearly appears that these are the real and, if possible, essential definitions of what is the proper and formal object of each science (genus subiecti). But through various texts we find that the respective measurements of such formal or proper objects must also be counted as proper principles of the sciences.